Intraoperative tactics for the removal of a large intraocular forein body in combination with retinal detachment. Clinical case - M. S. Al-Astal; G. K. Zhurgumbayeva; D. R. Kyrykbaev; S. K. Sambet (Российский офтальмологический журнал, 2025)
Purpose: analysis of a clinical case: removal of IOFB in combination with retinal detachment. This report presents and describes a clinical case of removing an intraocular foreign body (IOFB) diascloerally, with the elimination of retinal detachment. Under our observation was a young patient who suffered domestic trauma to the left eye. A magnetic foreign body, presumably a “nail gun staple”, entered and injured the left eye 3 days before hospitalization at the Kazakhstan Scientific Research Institute of Eye Diseases in Almaty, Kazakhstan. The patient had previously undergone primary surgical treatment of corneal wound + traumatic cataract phacoaspiration at the place of residence. The consensus decision recommended surgical treatment with the choice of transvitreal access as the main approach to IOFB extraction. However, during the operation, considering the localization of the foreign body under the retina and its length, it became clear that it was impossible to remove the foreign body with transvitreal access, as this would lead to significant retinal trauma. Recommended: remove the foreign body diascloerally according to its localization and location. The choice of access, tactics, and the extent of surgical intervention is finally decided intraoperatively and should be aimed at reducing eye trauma, especially the retina, during IOFB removal.